Towards Detecting Associations of Canine Astrovirus and Caliciviruses with Health and Living Characteristics of Dogs in Greece - Efthymia Stamelou; Konstantinos Papageorgiou; Dimitrios Papadopoulos; Georgios Delis; Dimitrios Chatzopoulos; Zoi Athanasakopoulou; Efstratios Moschidis; Evanthia Petridou; Spyridon K. Kritas (Pathogens)
Astroviruses and caliciviruses are important causative agents of gastroenteritis in humans worldwide. They have been detected in a variety of animal species, including dogs, but their role in the induction of disease in animals remains uncertain. In a molecular study that was conducted in Greece, including healthy and gastroenteritis-affected dogs of different ages, astrovirus (AstV) and sapovirus (SaV) were detected in 15% and 26% of the examined animals, respectively. A specialized questionnaire was filled out for each of the dogs participating in the study, including information about different characteristics and risk factors that could possibly affect their health status. This information was analyzed with the use of two innovative statistical methods, i.e., a Multiple Correspondence Analysis (MCA) and the Ascending Hierarchical Classification (AHC). Based on their results, it was possible to define various groups of dogs based on their characteristics. AstV seems to occur more often in low-health-status dogs, usually mongrels, living in rural areas, showing vomit, diarrhea, and diet changes. Dogs of this group usually live with other pets in the same household and have frequent contact with stray animals. The presence of SaV does not seem to be associated with any of the examined factors.